2014
DOI: 10.1021/co500005x
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Designed Library of Linear Helical Peptides: An Exploratory Tool in the Discovery of Protein–Protein Interaction Modulators

Abstract: Protein-protein interactions (PPIs) have emerged as important targets for pharmaceutical intervention because of their essential role in numerous physiological and pathological processes, but screening efforts using small-molecules have led to very low hit rates. Linear peptides could represent a quick and effective approach to discover initial PPI hits, particularly if they have inherent ability to adopt specific peptide secondary structures. Here, we address this hypothesis through a linear helical peptide l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 74 publications
0
21
0
Order By: Relevance
“…220,240 Notably, peptides patterned after this domain in TRPV1 channels inhibit receptor function, 228 indicating that this domain may also be a novel site for drug intervention in TRPM8 channels. Up to date, the destabilization of protein-protein interactions (PPI) within ion channels has barely been studied, 241 but most probably the application of strategies followed for other PPIs could also be relevant for TRPM8 drug discovery.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…220,240 Notably, peptides patterned after this domain in TRPV1 channels inhibit receptor function, 228 indicating that this domain may also be a novel site for drug intervention in TRPM8 channels. Up to date, the destabilization of protein-protein interactions (PPI) within ion channels has barely been studied, 241 but most probably the application of strategies followed for other PPIs could also be relevant for TRPM8 drug discovery.…”
Section: Summary and Future Perspectivesmentioning
confidence: 99%
“…We had previously described a collection of linear 13-mer peptide library, de novo designed for adopting helical conformations. Our hypothesis was based on the fact that α-helices are the secondary structure element most frequently involved in PPIs [ 15 ]. They were designed to fix a combination of either three aromatic—or two aromatic and one aliphatic—residues on one face of the helix (Ac-SSEE X 5 ARN X 9 AA X 12 N-NH 2 ), taking into account that frequently only the hydrophobic face of the helix is involved in binding, and also that key residues for affinity are located at relative positions i , i + 3( i + 4), i + 7.…”
Section: Introductionmentioning
confidence: 99%
“…In both cases, the protein–protein contact takes place through interfaces in which the mediation of a hydrophobic α-helix is essential. The results of the appropriate binding experiments showed that some of the tested peptides were able to mimic p53 and VEGF ‘hot-spots’, binding with their complementary proteins MDM2 (murine form of the HDM2 suppressor factor) and VEGFR1, respectively, and finally hampering their interaction with the respective partners, p53 and VEGF [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9,11 It is well known that the TRP domain of the different transient potential receptor channels contains various sets of hydrophobic residues, involved in channel assembly and activation. 13 Esters 1a-i, 2a-j, 3a-e were prepared by acylation of the corresponding alcohols with either acetic anhydride (esters 1a, 2a, 3a) or the appropriate carboxylic acids, using N-ethyl-N 0 -(3-dimethylaminopropyl)carbodiimide hydrochloride (EDC) as the carboxylate activator and 4-dimethylaminopyridine (DMAP) as the nucleophilic catalyst (esters 1b-i, 2b-j, 3b-e) (Scheme 1). Amides 1j,k and 2k,l were prepared by condensation of geranylamine (4a) and nerylamine (4b), respectively, with the appropriate carboxylic acids, using 1-hydroxybenzotriazole (HOBt)/EDC as the carboxylate activator (Scheme 2).…”
mentioning
confidence: 99%